A Semantic Analysis of Referential and Contextual Meaning in The “Tortoise and the Hare”: Rob John - Fina Yanti Sianturi; Bernieke Anggita Ristia DaAmanik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates referential and contextual meaning in The Tortoise and the Hare by Rob John through a qualitative semantic approach grounded in textual analysis and narrative interpretation. The research aims to examine how literal lexical references interact with contextual and symbolic meanings in constructing the moral discourse of the narrative. The primary data source consisted of lexical units, narrative events, and dialogues extracted from the fable, while the analytical framework was derived from semantic theories concerning referential meaning, contextual meaning, and discourse interpretation. The findings reveal that referential meaning appears through concrete lexical expressions associated with identifiable entities, actions, and spatial structures, whereas contextual meaning emerges through behavioral representation, symbolic interaction, and inferential interpretation embedded within the narrative sequence. The study also demonstrates that semantic interpretation in literary texts depends on the interrelation between denotative reference and contextual symbolism, enabling readers to derive ethical and pedagogical implications from seemingly simple narrative forms. The analysis confirms that semantic interpretation functions not merely as lexical decoding but as a multilayered interpretive process shaped by narrative context, symbolic structure, and reader cognition.